Combating Dual Challenges in Maize Under High Planting Density: Stem Lodging and Kernel Abortion - Shah, Adnan Noor; Tanveer, Mohsin; Abbas, Asad; Yildirim, Mehmet; Shah, Anis Ali; Ahmad, Muhammad Irfan; Wang, Zhiwei; Sun, Weiwei; Song, Youhong (Frontiers in Plant Science, 2021)
Abstract High plant density is considered a proficient approach to increase maize production in countries with limited agricultural land; however, this creates a high risk of stem lodging and kernel abortion by reducing the ratio of the biomass to the development of the stem and ear. Stem lodging and kernel abortion are major constraints in maize yield production for high plant density cropping; therefore, it is very important to overcome stem lodging and kernel abortion in maize. In this review, we discuss various morpho-physiological and genetic characteristics of maize that may reduce the risk of stem lodging and kernel abortion, with a focus on carbohydrate metabolism and partitioning in maize. These characteristics illustrate a strong relationship between stem lodging resistance and kernel abortion. Previous studies have focused on targeting lignin and cellulose accumulation to improve lodging resistance. Nonetheless, critical analysis of the literature showed that considering sugar metabolism and the examination of its effects on lodging resistance and kernel abortion in maize may provide considerable results to improve maize productivity. A constructive summary of management approaches that could be used to efficiently control the effects of stem lodging and kernel abortion is also included. The preferred management choice is based on the maize genotype; nevertheless, various genetic and physiological approaches can control stem lodging and kernel abortion. However, plant growth regulators and nutrient application can also help reduce stem lodging risk and kernel abortion in maize.